DOI: 10.4018/978-1-5225-5557-5.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Teaching First Aid, CPR, and AED Using Blended Learning in Academic Settings

Abstract: Due to the increase of accidents, incidences, and unexpected emergencies, knowledge of first aid, CPR, and AED skills is critical. It can make the difference between life and death and between complete recovery and permanent disability. Although numerous agencies such as the American Red Cross, American Safety and Health and Institute (ASHI), American Heart Association (AHA), and other organizations have trained millions of individuals in first aid, CPR, and AED, there is still a need to train more people espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A study investigating this phenomenon found that individuals whose training certificates were periodically renewed demonstrated superior skills and knowledge compared to those who obtained a single first aid certificate (Anderson, Gaetz, and Masse, 2011). Furthermore, the provision of effective first aid requires individuals to undergo professional training, enabling them to respond appropriately in emergency situations (Rotich and Elliott, 2019).…”
Section: Aim and Importance Of Researchmentioning
confidence: 99%
“…A study investigating this phenomenon found that individuals whose training certificates were periodically renewed demonstrated superior skills and knowledge compared to those who obtained a single first aid certificate (Anderson, Gaetz, and Masse, 2011). Furthermore, the provision of effective first aid requires individuals to undergo professional training, enabling them to respond appropriately in emergency situations (Rotich and Elliott, 2019).…”
Section: Aim and Importance Of Researchmentioning
confidence: 99%
“…However, there is still a need to train more people, especially the college-age population [13]. The administration of FA and Basic Life Support (BLS) as soon as possible after an injury may help reduce the rate of morbidity and mortality from schoolrelated industrial injuries [12,14].…”
Section: Introductionmentioning
confidence: 99%